Incidence of Contrast Induced Acute Kidney Injury, Its Risk Factors and In-Hospital Outcomes in Patients Undergoing Coronary Angiography and Angioplasty - Upadhaya, Prashun; Thapa, Pradeep; Gajurel, Ratna M; Sigdel, Mahesh R (Journal of Institute of Medicine Nepal, 2020)
Introduction Contrast-induced acute kidney injury (CI-AKI) is a serious complication of angiographic procedures with significant morbidity and mortality. We aimed to find the incidence, risk factors and outcomes of CI-AKI in patients who have undergone coronary angiography/angioplasty in a referral hospital in Nepal.MethodsIt was a descriptive observational study of consenting consecutive patients above 18 years undergoing coronary angiography/angioplasty at Manmohan Cardiothoracic Vascular and Transplant Centre, Nepal from July 2015 to September 2017. CI AKI was defined as an elevation of serum creatinine of >25% or ≥0.5 mg/dl (44 μmol/L) from baseline within 48 hour of exposure to contrast. Statistical analysis was performed using SPSS 18 software. Statistical analysis was completed using Student’s t-test, chi-square test and multivariable logistic regression analysis.ResultsOut of 240 patients, 156 (65%) were male, mean age was 60.36±11.29 years. Eighteen patients (7.5%) developed CI-AKI. Incidence of CI-AKI was 20% in patients with chronic kidney disease (CKD), 5.4% in diabetics, 13.6% in patients >70 years, 12.79 % in patients with anaemia and 12.3% in patients with prior contrast exposure. Multivariate logistic regression analysis found smoking and history of prior contrast exposure to be independent predictors for development of CI-AKI. Among patients with CI-AKI, one (5.88%) required dialysis and one (5.88%) died.ConclusionIncidence of CI-AKI after coronary angiography/angioplasty was 7.5%. Patients with prior contrast exposure and smoking were at significantly increased risk of CI-AKI; higher trend of CI-AKI was seen in patients with CKD, diabetes, elderly and anaemia.